INVESTIGATING THE USE OF WEB 2.0 TOOLS FOR TOEFL IBT SPEAKING PRACTICE TEST - Bury, Beata (Neofilolog, 2018)
The use of independent and integrated speaking tasks represents a distinctive element of the TOEFL iBT speaking exam. Integrated tasks that involve synthesizing and summarizing information presented in reading and listening materials have the potential to generate new test preparation strategies. Language teachers, whether in schools or colleges, have started using Web 2.0. tools in order to prepare students for language exams. It is asserted that Web 2.0. tools support active and meaningful learning and help students to express themselves on a particular subject. This paper describes the use of Web 2.0. tools to simulate TOEFL iBT-style speaking exercises and improve the students’ test taking ability in speaking during a course for kindergarten teachers in Andychów. Web-based activities were also implemented to help students overcome their fear of speaking. Also discussed are the main problems encountered, both pedagogical and technical, and what was done to solve them. Student feedback from an end-of-the-semester survey and from qualitative interviews is shared. The survey study shows that the use of Web 2.0. tools was a key feature of exam preparation on this intensive course. It is agreed that speaking skills of students can be improved through careful implementation of Web 2.0. tools.